Harmonizing Customary Law (Hukum Adat) with State Law in Natural Resource Management: A Case Study of Forest Communities in Kalimantan - Dara Vann; Vanna Sok; Rithy Vann; Arief Fahmi Lubis (Rechtsnormen: Journal of Law, 2025)
Background. The tension between customary law (hukum adat) and state law in natural resource management remains a central issue in Indonesia’s environmental governance, particularly in forest areas inhabited by indigenous communities. Customary practices have historically governed access, ownership, and conservation of forest resources, yet their legitimacy often conflicts with state-imposed regulatory frameworks that prioritize national economic interests. Purpose. The research aims to analyze the harmonization of customary and state legal systems in forest management within Kalimantan, exploring the juridical and sociocultural mechanisms that facilitate or hinder coexistence.   Method. A qualitative socio-legal research design was employed, integrating field observations, interviews with community leaders, and document analysis of statutory and customary legal instruments. Results. The findings reveal that effective harmonization depends on legal recognition of adat rights, participatory governance, and adaptive legal pluralism that bridges traditional norms with modern regulatory structures. However, conflicts persist due to overlapping jurisdiction, bureaucratic rigidity, and extractive economic policies.   Conclusion. The study concludes that sustainable forest governance requires an inclusive legal framework that institutionalizes customary law as a complementary not subordinate component of environmental regulation.